Intraocular Pressure Control after Trabeculectomy: A Comparison of Mitomycin C and Bevacizumab - Aftab Ahmed Khan, Sohail Ahmed Siddiqui, Mujahid Raza, Nisar Ahmed Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To analyze and compare the role of mitomycin C and bevacizumab in reducing the intraocular pressure post trabeculectomy. Study Design: Comparative analytical study Place and Duration of Study: Department of Ophthalmology, Indus Medical College, Tando Mohammad Khan from 1st October 2021 to 31st March 2022. Methodology: Sixty patients were enrolled. Patients were divided equally in two groups. Thirty patients were given mitomycin C in Group A while Group B were those 30 patients who were given bevacizumab in a randomized manner. All the cases underwent trabeculectomy and followed upto a year and results were compared. An examination using slit lamp biomicroscope was performed for thorough examination of anterior segments with intraocular pressure recording. Gonioscopy through Goldman-two mirror lens was conducted. Results: The mean age of the patients was 50.23±7.7 years with 41.6 % females and 58.3% males. The intraocular pressure was seen to be controlled in 23 patients at day 1 in Group A and 23 patients in group B. The comparative analysis of pre and post intraocular pressure after trabeculectomy has presented the significant reduction in Group A than Group B at day 1, 6th week as well as at 3rd month or 6th moth to a year. Conclusion: Mitomycin C as well as bevacizumab are highly effective in reducing intraocular pressure post trabeculectomy with mitomycin C being slightly better in efficacy than bevacizumab. Keywords: Intraocular pressure, Trabeculectomy, Effective, Efficacy